An Investigation of the Entropy Associated with a Collapsing Molecular Cloud - Gemechu Muleta Kumssa (Astronomy)
The investigation of entropy variation during the star formation process within collapsing molecular clouds represents a significant field of inquiry in astrophysics. As the cloud contracts, the presence of gaseous components contributes to an increase in entropy; however, the degree of this entropy change is contingent upon the spatial constraints imposed on the gases. In this research endeavor, I perform a comprehensive analysis of entropy dynamics on a microcosmic level within the contracting cloud, adhering to the tenets of the second law of thermodynamics. The initial focus centers on a turbulent cloud consisting of N particles, each with a mass of M, which succumbs to gravitational forces. It becomes evident that for the collapse to transpire, the gravitational energy must surpass the opposing pressure forces, resulting in the swift movement of particles throughout the cloud and ultimately facilitating a shift in entropy.